2008
DOI: 10.1109/led.2008.2000654
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiple-Gate Polycrystalline Silicon Nanowire Transistor Featuring an Inverse-T Gate

Abstract: A novel multiple-gate field-effect transistor with poly-Si nanowire (NW) channels is proposed and fabricated using a simple process flow. In the proposed structure, poly-Si NW channels are formed with sidewall spacer etching technique, and are surrounded by an inverse-T gate and a top gate. When the two gates are connected together to drive the NW channels, dramatic performance enhancement as compared with the cases of singlegate operation is observed. Moreover, subthreshold swing as low as 103 mV/dec at Vd = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…11 Recently we had proposed several simple nanowire ͑NW͒ TFT preparation methods without the need of expensive lithographic tools. 12,13 In this paper, we extended the results of a previous work 14 and investigated the impacts of independent double-gated ͑IDG͒ configuration and the channel film thickness on the performance of TFT SONOS devices.…”
Section: Effects Of Independent Double-gated Configuration On Polycrymentioning
confidence: 89%
“…11 Recently we had proposed several simple nanowire ͑NW͒ TFT preparation methods without the need of expensive lithographic tools. 12,13 In this paper, we extended the results of a previous work 14 and investigated the impacts of independent double-gated ͑IDG͒ configuration and the channel film thickness on the performance of TFT SONOS devices.…”
Section: Effects Of Independent Double-gated Configuration On Polycrymentioning
confidence: 89%
“…However, as compared with the metaloxide-semiconductor transistors built on bulk-Si, a large amount of defects contained in the poly-Si channel film would dramatically aggravate the device performance in terms of high subthreshold swing ͑SS͒ and OFF-state leakage current. 1 Such concern can be relieved by thinning the channel to reduce the amount of defects 4,5 and/or the adoption of a multiple-gated configuration to enhance the gate controllability. [5][6][7] The latter approach has also been widely investigated in devices with monocrystalline Si channel.…”
Section: Insight Into the Performance Enhancement Of Double-gated Polmentioning
confidence: 99%
“…1 Such concern can be relieved by thinning the channel to reduce the amount of defects 4,5 and/or the adoption of a multiple-gated configuration to enhance the gate controllability. [5][6][7] The latter approach has also been widely investigated in devices with monocrystalline Si channel. 8,9 By combining the above two approaches, SS smaller than 100 mV/dec can be achieved.…”
Section: Insight Into the Performance Enhancement Of Double-gated Polmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reduction of defect density and improvement of gate controllability via scale-down of the poly-Si NW channel have been reported. Some studies have even demonstrated the scale-down of the poly-Si NW without using advanced lithographic tools and have obtained excellent device characteristics [11]- [14]. Poly-Si NW TFTs with small gate length (< 0.1 μm) and very thin dielectrics have also been proposed to improved transfer characteristics [15], [16].…”
mentioning
confidence: 99%